Clinical learning experiences of nursing and midwifery students; a descriptive cross-sectional study - Sarah Ama Amoo; Nancy Innocentia Ebu Enyan (Elsevier, 2022)
Background: Clinical learning is important in nursing education, this is because it equips nursing students with the requisite skills to develop clinical competence. Understanding the factors that impact clinical learning could contribute to improving the effectiveness of clinical teaching and learning. The aim of this study was to assess clinical learning and its effectiveness among students of a nursing and midwifery training college in Cape Coast, Ghana. Methods: This was a quantitative study that adopted the descriptive cross-sectional design. Participants comprised 260 second and third year nursing and midwifery students, who were sampled using simple random sampling technique. There were 20 males and 240 females aged 19-36 years. Data were collected with a questionnaire and analysed using frequency counts, percentages and measure of central tendency. Results: Results revealed that though 80% (208) of participants always went to the clinical site with learning objectives, only 8% (21) were able to achieve their objectives always. Fifty percent (130) of participants learned through observation and imitation. Fifty-one percent (134) found it difficult to practice the theory they learn in school in the wards. On its effectiveness, 75% (195) of participants stated it was effective in improving clinical skills. In the clinical setting, students commonly learned by observing and imitating procedures. Though students get to improve on their clinical skills, they did not always achieve their learning objectives. There should be provision of needed material (equipment) and human (supervision) resources to help students achieve clinical goals.